Characterization of Ge-doped homoepitaxial layers grown by chemical vapor deposition - Sledziewski, Tomasz; Beljakowa, Svetlana; Alassaad, Kassem; Kwasnicki, Pavel; Arvinte, Roxana; Juillaguet, Sandrine; Zielinski, Marcin; Souliere, Veronique; Ferro, Gabriel; Weber, Heiko B.; Krieger, Michael (Materials Science Forum, 2014)
We have investigated the electrical properties of n-type 4H-SiC in-situ germanium-doped homoepitaxial layers grown by chemical vapor deposition. Germanium is an isoelectronic impurity and, therefore, not expected to contribute to the conductivity. However, Hall effect measurements taken on samples with and without germanium revealed an enhanced mobility by a factor of ≈2 at T ≈ 55 K in the germanium-doped sample despite equal free electron concentration and equal compensation. Deep level transient spectroscopy (DLTS) measurements taken on germanium-doped samples reveal negative peaks indicating the presence of charged extended defects. © (2014) Trans Tech Publications, Switzerland.
UnivIS-Import:2015-04-14:Pub.2014.nat.dphy.IAP.LAP.charac
Keywords: Admittance spectroscopy; DLTS; Ge-doping; Hall effect; Hall mobility

Doping of 4H-SiC with group IV elements - Krieger, Michael; Rühl, Maximilian; Sledziewski, Tomasz; Ellrott, Günter; Palm, Theresa; Weber, Heiko B.; Bockstedte, Michel Georg (Materials Science Forum, 2016)

Effect of germanium doping on electrical properties of n-type 4H-SiC homoepitaxial layers grown by chemical vapor deposition - Sledziewski, Tomasz; Vivona, M.; Alassaad, K.; Kwasnicki, P.; Arvinte, R.; Beljakowa, Svetlana; Weber, Heiko B.; Giannazzo, F.; Peyre, H.; Souliere, V.; Chassagne, T.; Zielinski, M.; et al. (Journal of Applied Physics, 2016)
The effect of germanium (Ge) on n-type 4H-SiC is experimentally studied by electrical characterization of homoepitaxial layers grown by chemical vapor deposition (CVD). Measurements show that electrical properties of epitaxial layers can be changed by intentional incorporation of germane (GeH4) gas during the deposition process. On the nanoscale, two-dimensional mappings acquired with conductive atomic force microscopy show preferential conductive paths on the surface of Ge-doped samples, which are related to the presence of this isoelectronic impurity. Hall effect measurements confirm that also macroscopic electrical properties of n-type 4H-SiC are improved due to incorporation of Ge into SiC during CVD growth. In particular, despite equal free electron concentration, enhanced mobility in a wide temperature range is measured in Ge-doped samples as compared to a pure 4H-SiC layer. Based on our results from Hall effect measurements as well as admittance spectroscopy and deep level transient spectroscopy, it is speculated that Ge influences the generation and annealing of other point defects and thus helps to reduce the total concentration of defects. Published by AIP Publishing.

Passivation and generation of states at P-implanted thermally grown and deposited n-type 4H-SiC / SiO2 interfaces - Sledziewski, Tomasz; Weber, Heiko B.; Krieger, Michael (Materials Science Forum, 2016)

Reduction of implantation-induced point defects by germanium ions in n-type 4H-SiC - Sledziewski, Tomasz; Ellrott, Günter; Rösch, Willi; Weber, Heiko B.; Krieger, Michael (Materials Science Forum, 2015)
We have investigated the electrical properties of germanium-implanted n-type 4H-SiC epitaxial layers. Deep level transient spectroscopy (DLTS) was employed in order to study the influence of germanium ions on implantation-induced point defects. In particular, we observe a decrease of the concentration of Z1/2 defect with increasing dose of implanted germanium.
UnivIS-Import:2017-12-18:Pub.2015.nat.dphy.IAP.LAP.reduct
Keywords: 4H-SiC; DLTS; Ion implantation; Point defects